2021
DOI: 10.5937/sjm16-33274
|View full text |Cite
|
Sign up to set email alerts
|

Perception of selected strategic management factors of SME in V4 countries

Abstract: The objective of the paper was to present current theoretical findings in the area of strategic management of small and medium-sized enterprises (SMEs) in the Visegrad Four (V4) countries. Within the stated objective, the weight of individual strategic management factors was quantified and trends in the Czech Republic were compared with other V4 countries. Empirical research was conducted between October 2019 and March 2020 in V4 countries by means of an online questionnaire. The overall number of accepted que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Thus, the results did not confirm that all factors from x1 to x7 influenced individual countries. Each country has some differences, as pointed out by several previous studies (Belás et al, 2021;Metzker & Zvarikova, 2021;Zvarikova et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the results did not confirm that all factors from x1 to x7 influenced individual countries. Each country has some differences, as pointed out by several previous studies (Belás et al, 2021;Metzker & Zvarikova, 2021;Zvarikova et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…According to Virglerova et al (2020), there are other types of risks that can result in financial losses that need to be managed besides financial ones. In a global economic environment, companies need to manage strategic risks effectively to improve their competitiveness (Belás et al, 2021). Risks related to bamboo handicrafts include market risk, operational risk, and financial risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…COVID-19 also disrupted the labour market (Ancillo et al, 2021;Belás et al, 2021). Although the labour demand rebounded in the short term, Krumel et al (2021) showed that there is a labour shortage because of the decreases in salaries and in the quality of required skills.…”
Section: Literature Reviewmentioning
confidence: 99%